Mitigation of Enterprise Supply Chain by Integrating Fine-Kinney Method And Analytical Hierarchy Process (AHP) - Hana Catur Wahyuni; Steve Fany Amalia Haque (Universitas Muhammadiyah Sidoarjo, 2022)
PT. VUB is engaged in construction manufacturing which is under the auspices of PT. Semen Indonesia Beton which will then be sent to retailers or distributors throughout Indonesia. The problem faced today is that companies often experience out of stock due to the fluctuating number of requests and inappropriate raw material planning that hampers the production process. This study aims to identify risky activity factors, plan appropriate strategies to minimize risk factors that occur in the company and provide solutions that can improve supply chain performance. The method used in supply chain risk mitigation at PT. VUB BM plant Pandaan is Fine-Kinney which aims to expose the value of risk factors based on the level of impact of the severity of the risk, and the solution uses the Anaytical Hierarchy Process (AHP) method as a determinant of the weight of risk mitigation strategies in the supply chain. From the results of risk identification at PT. VUB BM Pandaan was found that the highest risk occurred in the variable lack of K3 implementation in the production process with a risk rating value of 420 which has a very high risk factor because it can cause work accidents to employees. And the results of risk analysis with the criteria of raw material suppliers, production processes and distributors using the AHP method obtained 7 alternative supply chain risk mitigation strategies. With this research, it is hoped that it can help companies to reduce the risk of the company's supply chain.